La victoire d'André Jarlan la naissance d'une affaire pendant la dictature militaire chilienne - Cortés, Alexis (Social compass, 2018)
André Jarlan was a French priest murdered by the Chilean police during a protest against the dictatorship in the working-class neighbourhood of La Victoria. In this article, I will show how the Jarlan case can be framed in what the sociology of Luc Boltanski calls affaire. The Jarlan case, through the denunciation of the murder, contributed to develop a generalisation of the critique of the dictatorship, giving visibility to other crimes and allowing the re-humanization of its victims. This case shows that the critical capacities of people and the claim for justice can be mobilized with success even in an unfavourable situation such as a dictatorship. The condition of the victim (a priest), the accuser (the Catholic Church), the executioner (the dictatorship), and the cause (the pobladores) are the elements that will give exemplarity to this case that morally defeats the Chilean dictatorship.